2022
DOI: 10.3390/metabo12020104
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Intestinal Permeability are Reflected by Changes in the Urine Metabolome of Young Autistic Children: Preliminary Results

Abstract: Several metabolomics-based studies have provided evidence that autistic subjects might share metabolic abnormalities with gut microbiota dysbiosis and alterations in gut mucosal permeability. Our aims were to explore the most relevant metabolic perturbations in a group of autistic children, compared with their healthy siblings, and to investigate whether the increased intestinal permeability may be mirrored by specific metabolic perturbations. We enrolled 13 autistic children and 14 unaffected siblings aged 2–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…In this study, elevated levels of urinary nicotinurate and 1-methyl-NAM in ASD children with increased gut permeability revealed disruptions in the tryptophan-NA metabolic pathway, whereas the presence of these catabolites in the urine indicated a shift in tryptophan metabolism from serotonin biosynthesis to the formation of NA [88]. It has been proposed that, in children with ASD, the high level of urinary 1-methyl-nicotinamide could reflect an increased demand for NA [88,118].…”
Section: Linking Intestinal and Neurological Conditions: Autism Spect...mentioning
confidence: 59%
See 1 more Smart Citation
“…In this study, elevated levels of urinary nicotinurate and 1-methyl-NAM in ASD children with increased gut permeability revealed disruptions in the tryptophan-NA metabolic pathway, whereas the presence of these catabolites in the urine indicated a shift in tryptophan metabolism from serotonin biosynthesis to the formation of NA [88]. It has been proposed that, in children with ASD, the high level of urinary 1-methyl-nicotinamide could reflect an increased demand for NA [88,118].…”
Section: Linking Intestinal and Neurological Conditions: Autism Spect...mentioning
confidence: 59%
“…Remarkably, gastrointestinal issues, such as chronic diarrhea, constipation, irritable bowel syndrome, and gastroesophageal reflux are common comorbidities in ASD, likely arising from a vicious cycle that involves intestinal dysbiosis, intestinal mucosa inflammation and increased intestinal permeability compounded by food selectivity [88]. In this study, elevated levels of urinary nicotinurate and 1-methyl-NAM in ASD children with increased gut permeability revealed disruptions in the tryptophan-NA metabolic pathway, whereas the presence of these catabolites in the urine indicated a shift in tryptophan metabolism from serotonin biosynthesis to the formation of NA [88]. It has been proposed that, in children with ASD, the high level of urinary 1-methyl-nicotinamide could reflect an increased demand for NA [88,118].…”
Section: Linking Intestinal and Neurological Conditions: Autism Spect...mentioning
confidence: 99%
“…On this subject, in recent years, the emergence of metabolomics has made it possible to detect alterations in metabolites in ASD effectively [ 148 ], and major metabolomic studies on blood samples are summarized in Table 1 . Decreased levels of antioxidants, high levels of bacterial-derived phenolic compounds and a high concentration of SCFAs have been reported to be found in the urine, stools and blood of children with autism [ 149 , 150 , 151 , 152 ].…”
Section: Dysbiosis In Asd Patientsmentioning
confidence: 99%
“…In addition, a subset of ASD children with increased gut permeability were identified using the lactulose:mannitol test. In these children, four additional gut-permeable metabolites (phenylacetyl glycine, fucose, nicotinurate, and 1-methyl-nicotinamide) were found in their urine, which were not seen in the urine of the remaining children with ASD [ 167 ]. In another urinary metabolomic study, the authors identified significant dysregulation to the purine, tyrosine, phenylalanine and tryptophan pathways, characterized by increased phenylalanine and decreased tyrosine levels.…”
Section: Gut Microbiota In Children and Adolescents With Asdmentioning
confidence: 99%